URBE: Applicazioni di Game engine per la valorizzazione del patrimonio culturale attraverso dinamiche di edutainment - Limoncelli, Massimo; Cangemi, Marco (Archeomatica, 2024)
During 2022, a research and experimentation project aimed at developing new interactive approaches in the use of cultural heritage was launched within the Virtual Archeology Laboratory of the University of Palermo. Through reflection on the experiences that have characterized the disciplinary field and the observation of the possibilities offered by the videogame world, we proceeded to define a protocol called URBE which provides for the development of simulation ecosystems, through game-type software engine, within which users play the role of protagonists of the proposed experience, being able to relate independently with the virtual resources. These elements have made it possible to develop edutainment dynamics with a strong communicative impact and a high degree of immersion which are proposed as an ideal solution in the context of the valorisation of cultural heritage.